AYURVEDIC MANAGEMENT IN THREATENED ABORTION AND FOETAL ANOMALY – A CASE REPORT (International Journal of Ayurveda and Pharma Research, 2020)
Congenital anomalies amount to 50% of causative factor to first trimester abortions. Ayurvedic Ante Natal Care is highly effective in maintaining a healthy pregnancy and delivering a healthy progeny. A 28 year old female with bleeding per vaginum which started at 5 weeks of pregnancy, was advised for Medical Termination of Pregnancy. But she wanted to try Ayurvedic management and was treated with Ayurvedic medicines. The bleeding stopped in 11 days and fetal pole was visualized. She had occasional spotting in between and was detected with long bone growth lower than the normal limit in her anomaly scan at 20 weeks of gestation. She was advised termination owing to the risk of fetal anomalies but she was unwilling and wanted to continue Ayurvedic treatment. She was explained regarding all the possible consequences of continuing the pregnancy and with the consent of the patient and her family Ayurvedic treatment was continued. She delivered a healthy male baby of birth weight 2.57kg through Lower Segment Caesarean Section at term with an APGAR score of 9 at 1 minute. The baby had no gross or obvious anomalies at birth. The present case demonstrates the effectiveness of Ayurvedic Ante Natal Care in positive prognosis of threatened abortion.